Gambaran Tingkat Psychological Distress Mahasiswa dan Hubungannya dengan Aksesibilitas Pelayanan Konseling Mahasiswa - Maharani, Winda (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2021)
The purpose of this research are to know the difference of psychological distress level among student based on his needs of university mental health care services, and also to know the reasons of using the university mental health care services. Subject are divided into 4 group. First, the group who needs university mental health care services on both 2010 and 2011, second is the group who doesn’t need university mental health care services on both 2010 and 2011, third is the group who needs university mental health care services only on 2010 and last is the group who needs university mental health care services only on 2011. This research using triangulation of study as a method to collect data. The result of this research revealed that there is no significant difference in level of psychological distress among 4 groups mentioned earlier. The result also revealed the reasons of using the BKM services is highly associated with accessibility of mental health care services issues.